PLATINUM GROUP ELEMENTS (PGE) AND OS ISOTOPIC GEOCHEMISTRY OF FERROMANGANESE CRUSTS FROM PACIFIC OCEAN SEAMOUNTS AND THEIR CONSTRAINTS ON GENESIS - Sun X.M.; Xue T.; He G.W.; Zhang M.; Shi G.Y.; Wang S.W.; Lu H.F. (My University, 2006)
Platinum group elements (PGE), Au contents and Os isotopic compositions in ferromanganese crusts and their basaltic substrates from the central and west Pacific Ocean were analyzed. The results show that their PGE and Au contents are quite high and greatly varied, the ∑PGE is (70.09 ~ 629.26) × 10-9 and the total Au is (0.60 ~ 26900) × 10-9 respectively. In the three-layered (outer, porous and compact layers) crusts, the ∑PGE contents of porous ((339.37 ~ 545.82) × 10-9) and compact ((280.09 ~ 629.26) × 10-9) layers are significantly higher than the outer ((70.09 ~ 133.27) × 10-9) layers. The single-layered crusts are also enriched in PGE (∑PGE = (83.94 ~ 479.75) × 10-9), and their Au contents are usually higher than the three-layered ones. In addation, ∑PGE and Au contents of ferromanganese crusts are much higher than that in the nodules (∑PGE = (101.57 ~ 155.83) × 10-9, Au = (1 - 4) × 10-9). Different sedimentary water depths and oxygen fugacity of the ambient sea water of the crust and nodules may be the major reason for their different PGE and Au contents. ∑PGE and Pt are positively correlated with Mn % but inversely correlated with Fe %, which is just contrary to that in nodules, suggesting that PGE in the crusts may mainly occur in manganese mineral phases such as vernadites (δ-MnO2), while the PGE in the nodules may predominantly occur in iron mineral phases such as goethites(FeOOH · nH2O). Chondrite-normalized patters and various geochemical parameters of PGE demonstrate that PGE and Au in the ferromanganese crusts were sourced from water/rock reaction between the basaltic substrates and seawater, and partly from extraterrestrial materials such as iron meteorite dusts, but not related to submarine hydrothermal venting. Calculation based on cobalt contents show that ferromanganese crusts in the west Pacific Ocean began to grow at about 42.5Ma, and underwent two growth hiatuses corresponding to the geological ages of 21.8Ma and 8.0Ma respectively. The growth rates of the outer, porous and compact layers are 2.64mm/Ma, 1.45mm/Ma and 1.06mm/Ma, and the 187Os/188Os of the corresponding ambient sea water are 0.948 ~ 0.953, 0.599 ~ 0.673 and 0.425 ~ 0.536 separately, implying that the outer layers contained more continental eroded dusts, while the sediments in the porous and compact layers were mainly sourced from submarine basalt alteration and extraterrestrial materials such as interplanetary dust particles (IDPs).
Keywords: FERROMANGANESE CRUSTS; OS ISOTOPIC COMPOSITION; PLATINUM GROUP ELEMENTS (PGE) GEOCHEMISTRY; POLYMETALLIC NODULES; SEAMOUNTS IN CENTRAL AND WEST PACIFIC OCEAN